The HIF target MAFF promotes tumor invasion and metastasis through IL11 and STAT3 signaling - Eui Jung Moon (Nature Portfolio, 2021)
Hypoxia plays a critical role in tumor progression including invasion and metastasis. Here, the authors screened several hypoxia inducible genes and identified the oncogenic role of MAFF in breast cancer metastasis and that it activates IL11/STAT3 pathway.